2019
DOI: 10.1039/c9tc04880d
|View full text |Cite|
|
Sign up to set email alerts
|

Interface-engineered reliable HfO2-based RRAM for synaptic simulation

Abstract: O3-based interface engineering dominates implementations of analog memory and synaptic simulation using reliable Pt/HfO2/TiN RRAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 34 publications
1
63
0
Order By: Relevance
“…In this review, we will present RRAM-related inorganic materials with oxides, solid electrolyte and two-dimensional (2D) materials. [9,20,75], NiO [8,12,76], TiO 2 [21,77,78], HfO 2 [60,79,80], ZnO [81][82][83], and ZrO 2 [22,84,85] are always playing main roles in materials application of RS medium. The first report of RS performance in binary metal oxides was proposed by Hickmott in 1962 [91], which demonstrated the RS characteristics of Al/Al 2 O 3 /Al device under the effect of an electric field.…”
Section: Thin Film Materials Of Rs Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we will present RRAM-related inorganic materials with oxides, solid electrolyte and two-dimensional (2D) materials. [9,20,75], NiO [8,12,76], TiO 2 [21,77,78], HfO 2 [60,79,80], ZnO [81][82][83], and ZrO 2 [22,84,85] are always playing main roles in materials application of RS medium. The first report of RS performance in binary metal oxides was proposed by Hickmott in 1962 [91], which demonstrated the RS characteristics of Al/Al 2 O 3 /Al device under the effect of an electric field.…”
Section: Thin Film Materials Of Rs Mediummentioning
confidence: 99%
“…Wang et al proposed an interface engineering method on ALD-based HfO 2 thin film with O 3 , which improved the performance of Pt/HfO 2 /TiN RRAM device [79]. It is reported that the best stability could be observed in the HfO 2 RRAM device with 20 pulses of O 3 treatment.…”
Section: Thin Film Materials Of Rs Mediummentioning
confidence: 99%
“…RRAMs based on various materials, including metal oxides [5,6], novel nanomaterials [7][8][9], and organics [10,11], have been proposed. Among them, RRAM based on hafnium oxide [12][13][14][15], which replaced SiO 2 as the gate dielectric of choice below the 45 nm node [16,17], has been widely studied due to its high switching stability. There are still many challenges to overcome before RRAMs can be used as commercial memory, such as switching uniformity, overshoot current during forming or set process, leakage current in integrated arrays, and so on [4,18].…”
Section: Introductionmentioning
confidence: 99%
“…During the application of the negative pulse train, again gradually the weak filaments formed at both interfaces. To implement more accurately synaptic efficiency, of the tri-layer TaN/HfO 2 /Al 2 O 3 /HfO 2 /ITO memristor, negative pulse, and positive depression pulse with increasing amplitude were applied for potentiation and depression characteristics [ 47 , 48 , 49 ]. For potentiation and depression, increasing the pulse amplitude from −0.6 to −1.4 V, with a −0.05 V step, and 0.8 to 1.6 V, with a 0.05 V step, respectively, was applied to each tri-layer RRAM device.…”
Section: Resultsmentioning
confidence: 99%
“…Positive synaptic weight change is observed in the IInd quadrant when Δt increases from 0 to ‒100 µs, which indicates synaptic potentiation, and negative synaptic weight change observed in the IVth quadrant when Δt varies from 0 to 100 µs is described as synaptic depression. The change of synaptic weight can be described as follows: where A + and A ‒ are the synapse maximum weights at Δt = 0, and τ + and τ ‒ are the broadening of the STDP window [ 48 ]. From Figure 6 d, it can be found that the maximum change in synaptic weight [ΔW(ΔG/G) = (G fin − G min )/G min ] for positive Δt was 98.3% and for negative Δt was −94.8%, which is very symmetric for tri-layer RRAM device.…”
Section: Resultsmentioning
confidence: 99%